2017
DOI: 10.7554/elife.27612
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific regulation of BMP signaling by Drosophila N-glycanase 1

Abstract: Mutations in the human N-glycanase 1 (NGLY1) cause a rare, multisystem congenital disorder with global developmental delay. However, the mechanisms by which NGLY1 and its homologs regulate embryonic development are not known. Here we show that Drosophila Pngl encodes an N-glycanase and exhibits a high degree of functional conservation with human NGLY1. Loss of Pngl results in developmental midgut defects reminiscent of midgut-specific loss of BMP signaling. Pngl mutant larvae also exhibit a severe midgut clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 80 publications
6
82
0
Order By: Relevance
“…In fact, they showed that chemical inhibition of NGLY1 function potentiates cytotoxicity caused by proteasome inhibition in human cancer cell lines ( Tomlin et al 2017 ), which mirrors the observation in nematodes that png-1 loss-of-function mutants are extremely hypersensitive to proteasome inhibition by bortezomib ( Lehrbach and Ruvkun 2016 ). Jafar-Nejad and colleagues showed that the fly NGLY1/Pngl is required during embryonic and larval development in Drosophila for post-translational processing of Dpp , the fly homolog of the conserved bone morphogen protein (BMP) family ( Galeone et al 2017 ), opening up the possibility that NGLY1 is required for the function of multiple glycoprotein clients.…”
mentioning
confidence: 99%
“…In fact, they showed that chemical inhibition of NGLY1 function potentiates cytotoxicity caused by proteasome inhibition in human cancer cell lines ( Tomlin et al 2017 ), which mirrors the observation in nematodes that png-1 loss-of-function mutants are extremely hypersensitive to proteasome inhibition by bortezomib ( Lehrbach and Ruvkun 2016 ). Jafar-Nejad and colleagues showed that the fly NGLY1/Pngl is required during embryonic and larval development in Drosophila for post-translational processing of Dpp , the fly homolog of the conserved bone morphogen protein (BMP) family ( Galeone et al 2017 ), opening up the possibility that NGLY1 is required for the function of multiple glycoprotein clients.…”
mentioning
confidence: 99%
“…NGLY1 also regulates NFE2L1-mediated mitochondrial function (Kong et al, 2018) and inflammation (Yang et al, 2018). NGLY1's deglycosylation activity was also shown to regulate tissue-specific bone morphogenetic protein (BMP) signaling in a Drosophila model (Galeone et al, 2017). Together, these studies suggest a more diverse direct or indirect role for NGLY1 in cellular signaling, which might explain the wide array of symptoms experienced by NGLY1-deficient patients.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, they showed that chemical inhibition of NGLY1 function potentiates cytotoxicity caused by proteasome inhibition in human cancer cell lines (Tomlin, 2017), which mirrors the observation in nematodes that png-1 loss-of-function mutants are extremely hypersensitive to proteasome inhibition by bortezomib (Lehrbach, 2016). Jafar-Nejad and colleagues showed that the fly NGLY1/Pngl is required during embryonic and larval development in Drosophila for post-translational processing of Dpp, the fly homolog of the conserved bone morphogen protein (BMP) family (Galeone, 2017), opening up the possibility that NGLY1 is required for the function of multiple glycoprotein clients.…”
Section: Introductionmentioning
confidence: 72%